The wild at home and the magic of contact. Stories about wild animals and spirits from Amudisy Evenki hunters and reindeer herders - Simonova, Veronika V. (Études mongoles et sibériennes, centrasiatiques et tibétaines, 2018)
This paper is about human-animal spiritual relations among Amudisy Evenki hunters and reindeer herders of Kalar district (Zabaikal region) in Siberia. Based on narratives describing the practice of bringing wild animals into human places, this anthropological study examines the network of relations between human and non-human actors in an attempt to answer the following questions: why do Evenki hunters bring wild animals into their camps? Why are they so interested in observing the ways in which animals expose themselves and become a part of a human world? Why do “human nature” (chelovecheskaia priroda) (as it is called by our informants) and wild animals share certain similarities in local spiritual beliefs? By creating a dialogue between ethnographic examples and the theories of mimesis and perspectivism, this paper shows that this complex subject should be approached in terms of a “magic of contact”. This is also true of local perednik beliefs, where the human and animal worlds coincide: in such beliefs, human nature (chelovecheskaia priroda) is held to be partially constituted by an animal spirit. The analysis of data as well as writing up was sponsored by RSF grant 14-18-02785. Cet article porte sur les relations spirituelles entre humains et animaux chez les Évenks chasseurs et éleveurs de rennes d’Amudisy, dans le district de Kalar (région de Zaibaikal) en Sibérie. Basé sur l’ethnographie de récits et de souvenirs recueillis auprès des éleveurs de rennes de cette région, présentant comment des animaux sauvages ont été rapportés sur les lieux d’habitation des humains, cet article examine un réseau de relations entre des acteurs humains et non-humains, et tente de répondre aux questions suivantes : Pourquoi les chasseurs évenks ont-ils besoin de rapporter un animal sauvage sur leurs campements ? Pourquoi sont-ils tant enclins à observer la façon dont un animal sauvage se dévoile et devient une partie du monde humain ? Pourquoi, ce que les informateurs appellent « la nature des humains » (chelovecheskaia ...